Depolymerization of waste polyethylene to linear alkenes via sequential dehydrogenation and metathesis - Khopade, Kishor V.; Rajput, Nikhita S.; Rangappa, Raghavendrakumar; Barsu, Nagaraju; Chikkali, Samir H. (Green Chemistry, 2024)
Polyethylene (PE) is the most abundantly sourced plastic and significant efforts are needed for its end-of-life management. The deconstruction of PE is an uphill task and requires the breaking of highly stable C-C bonds. Here we demonstrate that PE can be deconstructed to value-added dodecene, along with other long-chain alkenes. The PCP-iridium complex catalyzes the dehydrogenation of commercial and post-consumer polyethylene waste to produce dehydrogenated polyethylene (DHP) with 0.5-1.0% unsaturation. The DHP was subjected to an ethylene cross-metathesis reaction in the presence of suitable catalysts. Through meticulous optimization of reaction parameters, 63% selectivity toward dodecene, with 26% overall yield, was achieved. The practical significance of our method has been demonstrated by subjecting post-consumer plastic waste to dehydrogenation followed by ethylene metathesis to produce dodecene as a major product, together with long-chain alkenes. The PE deconstruction has been confirmed by recording molar mass before and after depolymerization using high-temperature gel permeation chromatography. The existence of dodecene has been unambiguously ascertained using GC, GC-MS, NMR, and IR spectroscopy. Thus, these results demonstrate the conversion of waste PE to value-added dodecene and long-chain alkenes under mild reaction conditions.